The Impact of the Ecological Situation on Blood Parameters of Pigeons - Zh. Kizatova, Maigul; N. Alibayeva, Bakhit; T.Azimova, Sanovar; K. Iskakova, Galiya; S. Nabiyeva, Zhanar; T. Uvakasova, Gulshat (International Journal of Psychosocial Rehabilitation, 2024)
The authors of the research studied the ecological situation in Almaty, Kazakhstan, using rock pigeons as indicators. Pigeons were captured in three areas of the city characterized by different ecological conditions. They measured the content of heavy metals (lead and cadmium) in the feathers and internals of the birds. They determined the morpho-functional peculiarities, as well as the hematological and biochemical blood parameters of the species. The study of hematological blood parameters revealed an increase in the number of red cells in the blood of birds from areas having an unfavourable ecological situation. The biochemical blood analysis of birds from areas having an unfavourable ecological situation showed an increase in the glucose and urea levels in blood serum, which can be used as a new biomarker for studies of bioindicators on the example of rock pigeons.